2018
DOI: 10.1002/1873-3468.12991
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucose‐stimulated insulin secretion by ATPase Inhibitory Factor 1 (IF1)

Abstract: ATPase Inhibitory factor 1 (IF1) is an endogenous regulator of mitochondrial ATP synthase, which is involved in cellular metabolism. Although great progress has been made, biological roles of IF1 and molecular mechanisms of its action are still to be elucidated. Here, we show that IF1 is present in pancreatic β-cells, bound to the ATP synthase also under normal physiological conditions. IF1 silencing in model pancreatic β-cells (INS-1E) increases insulin secretion over a range of glucose concentrations. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 53 publications
5
42
0
Order By: Relevance
“…C0018009). The results were invariant of the source as documented in previous reports [ 8 , 11 , 12 , 38 , 39 ]. Cells were cultivated with 11-mM glucose in RPMI 1640 medium with l -glutamine, supplemented with 10-mM HEPES, 1-mM pyruvate, 5% ( v/v ) fetal calf serum, 50-μmol/L mercaptoethanol, 50 IU/mL penicillin and 50-μg/mL streptomycin [ 38 , 39 ].…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…C0018009). The results were invariant of the source as documented in previous reports [ 8 , 11 , 12 , 38 , 39 ]. Cells were cultivated with 11-mM glucose in RPMI 1640 medium with l -glutamine, supplemented with 10-mM HEPES, 1-mM pyruvate, 5% ( v/v ) fetal calf serum, 50-μmol/L mercaptoethanol, 50 IU/mL penicillin and 50-μg/mL streptomycin [ 38 , 39 ].…”
Section: Methodssupporting
confidence: 83%
“…We found that also the inhibitory factor IF1 of the mitochondrial ATP synthase belongs to the key proteins, ensuring the physiological range of the glucose sensor [ 11 , 12 ]. The IF1 slightly inhibits synthesis of ATP, thus setting the range for elevation of phosphorylating respiration and insulin release above 3-mM glucose [ 11 , 13 ], with half-activation between 3.5 and 4-mM and saturation above 8-mM glucose [ 11 , 12 ]. When such a slight in vivo inhibition was largely cancelled using the silencing of IF1, the elevation of respiration and OXPHOS occurred at very low glucose concentration approaching to zero [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low mitochondrial ATP synthesis efficiency thus appears to ensure that the membrane potential as well as the mitochondrial and cytosolic ATP/ADP ratios are kept relatively low when insulin secretion is not required. Interestingly in this respect, ATPase inhibitory factor 1 has recently also been shown to dampen insulin secretion from insulinoma cells at basal glucose concentrations through inhibition of ATP synthesis [40] .…”
Section: Control Of Atp Flux By Atp Supplymentioning
confidence: 99%
“…The recently discovered aspect has explained the adjustment of the range of glucose concentrations for the glucose sensor [ 16 ]. Surprisingly, this is ensured by the inhibitory factor protein IF-1 of the mitochondrial ATP-synthase.…”
Section: Introductionmentioning
confidence: 99%